2018
DOI: 10.1167/iovs.17-23042
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Soluble CD14 in the Aqueous Humor and Hyperreflective Foci on Optical Coherence Tomography in Patients With Diabetic Macular Edema

Abstract: Citation: Lee H, Jang H, Choi YA, Kim HC, Chung H. Association between soluble CD14 in the aqueous humor and hyperreflective foci on optical coherence tomography in patients with diabetic macular edema. Invest Ophthalmol Vis Sci. 2018;59:715-721. https://doi.org/10.1167/ iovs. PURPOSE. To investigate the associations between soluble CD14 (sCD14), a cytokine released by microglia and macrophages, and hyperreflective foci (HF) and various characteristics of spectral-domain optical coherence tomography (SD-OCT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
85
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 26 publications
1
85
0
2
Order By: Relevance
“…The authors found both higher levels of sCD14, and increased number of HF in the inner retina compared to controls, and concluded that, since sCD14 is released by retinal microglia, HF might represent aggregates of activated microglial cells in DME eyes. 1 The presence of and changes in OCT HF, also called hyperreflective spots, have been previously described in detail in diabetic eyes and reported to depend on activated microglia. [2][3][4][5] DME-affected eyes treated with intravitreal anti-VEGF and steroids have also been investigated, demonstrating a reduction of HF number with both treatments-confirming HF as a retinal inflammatory biomarker.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…The authors found both higher levels of sCD14, and increased number of HF in the inner retina compared to controls, and concluded that, since sCD14 is released by retinal microglia, HF might represent aggregates of activated microglial cells in DME eyes. 1 The presence of and changes in OCT HF, also called hyperreflective spots, have been previously described in detail in diabetic eyes and reported to depend on activated microglia. [2][3][4][5] DME-affected eyes treated with intravitreal anti-VEGF and steroids have also been investigated, demonstrating a reduction of HF number with both treatments-confirming HF as a retinal inflammatory biomarker.…”
mentioning
confidence: 89%
“…We read with great interest the article titled ''Association Between Soluble CD14 in the Aqueous Humor and Hyperreflective Foci on Optical Coherence Tomography in Patients with Diabetic Macular Edema'' by Lee et al 1 The authors investigated the expression of soluble CD14 (sCD14) in aqueous humor (AH) samples of patients with diabetic macular edema (DME), and the presence of hyperreflective foci (HF) on spectral-domain optical coherence tomography (SD-OCT) in these eyes. The authors found both higher levels of sCD14, and increased number of HF in the inner retina compared to controls, and concluded that, since sCD14 is released by retinal microglia, HF might represent aggregates of activated microglial cells in DME eyes.…”
mentioning
confidence: 99%
“…Previously, HF were suspected as subclinical features of lipoprotein extravasation or migrating pieces of retinal pigmented epithelium [36,37]. However, recent reports suggested that HF can be activated forms of microglia and markers of inflammation [38,39]. On the other hand, EZ integrity reflects the health of the photoreceptor layer; EZ disruption is associated with a poor visual prognosis in DME patients [40].…”
Section: Discussionmentioning
confidence: 99%
“…We would like to convey our gratitude to Midena et al 1 for their thoughtful letter to the editor and their insightful comment regarding our article. 2 As shown in a previous study by Vujosevic et al, 3 the reflectivity of hyperreflective foci (HF), as aggregates of retinal microglial cells, might be lower than that of the retinal pigment epithelium (RPE) and could be similar to that of the retinal nerve fiber layer (RNFL). We also agree with the opinion that any investigation of HF regarding optical coherence tomography (OCT) in diabetic eyes should be more precise to avoid inconsistent results because counting HF in diabetic macular edema (DME) could be fairly subjective due to its similarity with other entities, such as hard exudate.…”
mentioning
confidence: 91%